Effects of 1 vs. 2 sessions per week of equal-volume sprint training on explosive, high-intensity and endurance-intensive performances in young soccer players - Marzouki, H.; Ouergui, I.; Doua, N.; Gmada, N.; Bouassida, A.; Bouhlel, E. (Biology of Sport, 2021)
The study aimed to evaluate the effects of 1 vs. 2 sessions per week of equal-volume sprint training on explosive, high-intensity and endurance-intensive performances among young soccer players. Thirtysix young male soccer players were randomly divided into 2 experimental groups that performed either a single weekly sprint training session (ST1, n = 18, age: 17.2 ± 0.8 years) or two weekly sprint training sessions (ST2, n = 18; age: 17.1 ± 0.9 years) of equal weekly and total volume, in addition to their regular soccer training regimen. Linear sprinting (10 m, 20 m, 30 m, and flying 10 m), T-test agility, countermovement jump (CMJ) and maximal oxygen consumption were assessed one week before (T1), in the middle (T2) and immediately after the 10 weeks of training (T3). A large magnitude and statistically significant main effect for time was found in all the assessed variables after both training interventions.